Esterification of palm fatty acid distillate using sulfate based catalysts - Nazratul Zaheera, Abdul Kapor (2019)
Research on biodiesel is worth to be explored persistently as a promising solution for depletion of fossil fuel and to counter the escalation of environmental disruptions. This study focuses on the production of biodiesel by esterification of palm fatty acid distillate (PFAD) using sulfuric acid and three types of sulfated metal oxides, SO42-/Fe2O3, SO42-/Al2O3 and sulfated deoiled spent bleaching clay (SO42-/DSBC). PFAD is by-product from palm oil refinery, containing high amount of free fatty acid. Characterisation test found that PFAD used in this study had acid value of 164.52 mgKOH/g, saponification value of 167.4 mgKOH/g, iodine value of 52.3 g I2/100g and moisture content of 0.26%. All three solid catalysts were prepared by wet impregnation using sulfuric acid via ultrasonic method. Ultrasonic method is chosen as it had been proven to aid in catalyst preparation and produce better performing catalyst compared to the conventional preparation. All the catalysts were characterised using FESEM-EDX, XRD, FTIR, Hammett indicators, TGA and BET. All the catalysts have acidity in the range of 1.8<pH<3.0. Among the catalysts, highest pore volume and surface area was recorded by SO42-/DSBC. Highest conversion obtained from among the heterogenous catalyst was SO42-/Fe2O3 with 87.81% methyl ester content at 90 °C, 5 h, 12:1 methanol to PFAD molar ratio and 7 wt% catalyst amount. Even with catalyst leaching, a conversion of 76.02% is achieved at fourth cycle of reusability. As for SO42-/DSBC, highest methyl ester obtained was 74.55% (at 110°C, 5 h, 12:1 methanol to PFAD molar ratio and 5 wt% catalyst amount) with fourth reusability gave 55.43% conversion, while SO42-/Al2O3 produced 67.81% methyl ester (at 110 °C, 9 h, 12:1 methanol to PFAD molar ratio and 7 wt% catalyst amount).